Combination etanercept and methotrexate provides better disease control in very early (≤4 months) versus early rheumatoid arthritis (>4 months and <2 years): post hoc analyses from the COMET study. Issue 6 (8th March 2012) - Emery, Paul; Kvien, Tore K; Combe, Bernard; Freundlich, Bruce; Robertson, Deborah; Ferdousi, Tahmina; Bananis, Eustratios; Pedersen, Ronald; Koenig, Andrew S
Abstract : Objective: The objective of this post hoc analysis was to test the benefits of treating very early rheumatoid arthritis (VERA; ≤4 months) using COMET trial data. Treatment response in VERA and early rheumatoid arthritis (ERA; >4 months to 2 years) with combination etanercept+methotrexate (ETN+MTX) or MTX monotherapy was compared. Methods: Data assessed at week 52 for baseline disease duration effect included remission (disease activity score (DAS)28 <2.6, SDAI ≤3.3, Boolean), low disease activity (LDA; DAS28 <3.2), Boolean components of remission and radiographic non-progression. Subjects who discontinued because of lack of efficacy were included as non-responders. Results: Higher proportions of VERA subjects achieved LDA (79%) and DAS28 remission (70%) than ERA (62%, 48%, respectively, p<0.05) with ETN+MTX. Such high responses with MTX monotherapy were not observed (VERA, LDA=47%, DAS28 remission=35%; ERA, 47% and 32% respectively, p>0.70 for each). Regardless of disease duration, no radiographic progression was seen in 80% of subjects with ETN+MTX. In contrast, a higher proportion of VERA subjects showed no radiographic progression compared with ERA subjects treated with MTX (73.9% vs 50%, p=0.01). Conclusions: Treatment of VERA with ETN+MTX provides qualitatively improved clinical outcomes not seen with MTX monotherapy, supporting the pivotal role of TNF inhibition in early disease.